Quantum-Chemical Simulation of the Cluster Structure of Liquid N-Heptanol - Golub, P.; Pogorelov, V.; Doroshenko, I. (Ukrainian Journal of Physics, 2012)
Different molecular aggregations formed in liquid heptanol due to the hydrogen bonding are investigated. Using the methods of quantum-chemical simulation, the preference of the aggregations involving more than 5 molecules is shown. The correctness of the conclusions is established by the comparison of the obtained results with experimental data.